2001
DOI: 10.1002/pc.10562
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modeling of tensile strength of particulate‐filled composites

Abstract: Based on Christen sen and Lo's (11) three‐layer sphere model, a two‐layer built‐in model is proposed to represent particulate‐filled composites. Following Papanico‐laou and Bakos' (14) procedure for a particle embedded in an infinite matrix model and using the rule‐of‐mixtures approach, formulations estimating the tensile strength of particulate‐filled composites are developed. Unlike Fapanicolaou and Bakos' formulations, the formulations developed in the present paper can characterize the effect of particle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…(30). Note that S depends on interface adhesion and varies from 9.8 Â 10 À4 to 1.74 Â 10 À3 MPa m. Li et al [171] developed a model that includes the effects of particle/matrix adhesion, particle size distribution, matrix degradation, etc. But the final expression of integration/summation is difficult to use in practical prediction of composite strength.…”
Section: Silica Weight Fraction (%)mentioning
confidence: 99%
See 2 more Smart Citations
“…(30). Note that S depends on interface adhesion and varies from 9.8 Â 10 À4 to 1.74 Â 10 À3 MPa m. Li et al [171] developed a model that includes the effects of particle/matrix adhesion, particle size distribution, matrix degradation, etc. But the final expression of integration/summation is difficult to use in practical prediction of composite strength.…”
Section: Silica Weight Fraction (%)mentioning
confidence: 99%
“…In the second case (n p = 1 À V p ), perfect bonding between particles and matrix is also used, but the matrix is assumed to degrade linearly with inclusion of particles due to the presence of particles and complications developed during the preparation of the composite. Using composite properties [171]: for glass particles -Young's modulus = 71 GPa, bulk modulus = 53.3 GPa, Poisson's ratio = 0.279, and epoxy -Young's modulus = 3.53 GPa, bulk modulus = 4.21 GPa, Poisson's ratio = 0.35 and tensile strength = 80 MPa, the effect of particle size on tensile strength is shown in Fig. 23 (where d p is mean particle size).…”
Section: Silica Weight Fraction (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the PLA-30 %SF composites exhibited an increase in specific tensile strength for both solid and microcellular components when compared to the neat PLA and PLA-10 %SF composites. It is possible that at increased fiber content (30 wt.%), the fibers were more densely packed and were able to increase the stress transfer ability of the PLA-30 %SF composites, thereby improving the tensile strength (Li et al, 2001). Other groups have shown that it is also possible that at high filler contents, the fibers were able to restrain the PLA matrix from deformation, allowing the highly-filled composite to withstand a higher stress at low strains (Bhardwaj et al, 2006;Whaling et al, 2006).…”
Section: Tensile Test Analysismentioning
confidence: 96%
“…The RoM can be used to approximate properties of composite materials such as the elastic modulus. Additional physical effects can be incorporated into the RoM formulation such as interfacial bonding between the composite materials; and the effect of particle size distributions and particle clustering within the composite (Li et al 2001). To quantify the effect of imperfect bonding between the individual Shackelford & Alexander (2000) components and the departure from perfectly formed idealized crystalline solids the parameter m b ∈ (0, 1] is introduced.…”
Section: Criteria For Electrostatic Disruption Of Spherical Dust Grainsmentioning
confidence: 99%